2011
DOI: 10.1152/ajpendo.00527.2010
|View full text |Cite
|
Sign up to set email alerts
|

Acipimox reduces circulating levels of insulin and associated neutrophilic inflammation in metabolic syndrome

Abstract: Metabolic syndrome is a proatherosclerotic condition clustering cardiovascular risk factors, including glucose and lipid profile alterations. The pathophysiological mechanisms favoring atherosclerotic inflammation in the metabolic syndrome remain elusive. Here, we investigated the potential role of the antilipolytic drug acipimox on neutrophil- and monocyte-mediated inflammation in the metabolic syndrome. Acipimox (500 mg) was orally administered to metabolic syndrome patients (n = 11) or healthy controls (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Furthermore, this article confirmed the inhibition of JNK2 as a promising therapeutic approach to reduce atherosclerosis at different stages [27]. The potential pro-atherosclerotic and pro-inflammatory activities driven by JNK phosphorylation were also confirmed in vitro in human inflammatory [28] and vascular cells [29], suggesting a relevance for controlling this pathway in hyperinsulinemic states associated with atherosclerotic diseases. The JNK-dependent downstream signalization was further investigated in vivo in mice and in vitro in endothelial cells.…”
Section: The Role Of Mitogen-activated Protein Kinases (Mapks)supporting
confidence: 54%
“…Furthermore, this article confirmed the inhibition of JNK2 as a promising therapeutic approach to reduce atherosclerosis at different stages [27]. The potential pro-atherosclerotic and pro-inflammatory activities driven by JNK phosphorylation were also confirmed in vitro in human inflammatory [28] and vascular cells [29], suggesting a relevance for controlling this pathway in hyperinsulinemic states associated with atherosclerotic diseases. The JNK-dependent downstream signalization was further investigated in vivo in mice and in vitro in endothelial cells.…”
Section: The Role Of Mitogen-activated Protein Kinases (Mapks)supporting
confidence: 54%
“…CRP, C-reactive protein; IL-6, Interleukin-6; IL-8, Interleukin-8; MCP-1, monocyte chemoattractant protein-1; MMP-9, metalloproteinase-9; TNF-a, tumor necrosis factor-a. (12,13,17,20,21)…”
Section: Discussionmentioning
confidence: 99%
“…The other approaches aim to stimulate or inhibit the three main pathways that are affected by CR. These approaches include (a) drugs that affect the IGF-1/insulin signaling pathway, principally the anti-diabetic biguanides (Anisimov, 2003;Anisimov et al, 2003;Anisimov, 2001) (b) anti-lipolytic drugs such as Acipimox Montecucco et al, 2011), (c) drugs that affect the sirtuin pathway such as resveratrol (Chen et al, 2008) (d) drugs that affect mTOR signaling such as rapamycin (Tsang et al, 2007). This is not an exclusive list as several other approaches have been adopted including the use of agonists of lipid activated nuclear receptors (Corton et al, 2004) or suggested but not yet investigated such as the use of ghrelin .…”
Section: The Theoretical Basis Of Developing Mimeticsmentioning
confidence: 99%
“…Acipimox (5-methylpyrazine-2-carboxylic acid-4-oxide), a nicotinic acid derivative has been shown to reduce insulin, and improve insulin resistance and oral glucose tolerance in cases of Metabolic Syndrome (Montecucco et al, 2011). The aforementioned improvements have particular significance in delaying the aging process, and once-a-week life-long administration of the Acipimox induced significant anti-aging effects similar to those of CR, without adversely effecting food intake or body weight .…”
Section: Antilipolytic Drugsmentioning
confidence: 99%